A secure and efficient authentication scheme for vehicle to grid in smart grid - Xiao, Nan; Wang, Zhaoshun; Sun, Xiaoxue (Frontiers in Physics, 2025)
As environmental issues and climate change worsen, Smart Grid has become a crucial technology for tackling energy challenges. Smart Grid substantially enhances the reliability, security and efficiency of power systems by integrating state-of-the-art communication, control and information technologies. As a crucial component of Smart Grid, Vehicle to Grid (V2G) facilitates bidirectional energy flow between electric vehicle (EV) and the grid. This not only optimizes energy utilization but also accelerates the large-scale adoption of EV, contributing to a more sustainable energy ecosystem. However, security and privacy concerns in V2G cannot be ignored, particularly regarding identity authentication and data protection. Therefore, enabling the secure transmission of users’ private information within V2G is crucial. This paper presents a secure and efficient authentication scheme for privacy preserving in V2G. The scheme validates vehicle user identities and leverages chebyshev chaotic maps along with hash function to enable V2G communication. It ensures both data integrity and user privacy during transmission, addressing key security concerns in V2G. Through formal security analysis, it is confirmed that the scheme can withstand common attacks. Additionally, detailed informal security discussions demonstrate that the scheme can resist known attacks and meet design objectives. Further performance evaluation shows that the proposed scheme balances efficiency and security.